2022
DOI: 10.1172/jci.insight.158754
|View full text |Cite
|
Sign up to set email alerts
|

Blocking cell cycle progression through CDK4/6 protects against chronic kidney disease

Abstract: and genome-wide association studies identified dachshund homolog 1 (DACH1), which suppresses tubular cell cycle progression, as having protective effects on CKD (7). Though suggestive that ongoing tubular cell cycling may be detrimental, few studies have directly manipulated cell cycle progression in the chronically injured kidney to determine how tubular cell cycle alters tubular injury and fibrosis.Most proximal tubules in the uninjured kidney are quiescent (G0) but, upon injury, reenter the cell cycle at G1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…These discrepant data likely indicate cell type-specific control of the cell cycle and underscore our incomplete understanding of the physiologic meaning of cell cycle states. Our data extend prior observations from other model systems that transient stalling or reversible prolongation of the cell cycle in G 2 is critical for successful repair of tissue injury (8,(91)(92)(93)(94). Cell cycle slowing after the acute kidney injury phase confers protection against chronic epithelial injury (92).…”
Section: Discussionsupporting
confidence: 85%
“…These discrepant data likely indicate cell type-specific control of the cell cycle and underscore our incomplete understanding of the physiologic meaning of cell cycle states. Our data extend prior observations from other model systems that transient stalling or reversible prolongation of the cell cycle in G 2 is critical for successful repair of tissue injury (8,(91)(92)(93)(94). Cell cycle slowing after the acute kidney injury phase confers protection against chronic epithelial injury (92).…”
Section: Discussionsupporting
confidence: 85%
“…In this study, we also made use of an in vitro model of CKD using primary PTCs treated with AA for 7 days. While no current in vitro model completely recapitulates the complexity of mammalian CKD, our group and others ha6ve demonstrated that this model can recapitulate some of the features of CKD observed in PTCs, namely dedifferentiation, G 2 /M arrest, and secretion of profibrotic cytokines ( 15 , 51 , 52 ). Therefore, we find this model useful for confirming the specific effects of genes or drugs on PTCs.…”
Section: Discussionmentioning
confidence: 82%
“…In our study, we uncover a highly novel finding that demonstrates that in the HK2 cell line, Hyper IL-6 not only promoted elevated expression of SGLT1 but also promoted proliferation of the cells ( Figure 8 , Figure 9 and Figure 10 ). Our findings are biologically relevant as the proximal tubule is particularly targeted during acute and chronic kidney injuries [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that blocking CDK4 will prevent damaged proximal tubule cells from proliferating during kidney injury. Injured proximal tubule cells promote tubulointerstitial fibrosis through production of proinflammatory and profibrotic cytokines [ 34 ]. In conclusion, blocking cell cycle progression by inhibiting CDK4 may protect against chronic kidney disease by preventing damaged proximal tubule cells from proliferating by reducing tubular injury, fibrosis and senescence [ 34 ].…”
Section: Discussionmentioning
confidence: 99%